Analisis Neraca Air pada Pengelolaan Air dalam System of Rice Intensification-Organik (SRI-Organik) di Jawa Barat, Indonesia - Chusnul Arif; Budi Indra Setiawan; Septian Fauzi Dwi Saputra; Masaru Mizoguchi (Jurnal Irigasi, 2019)
The System of Rice Intensification (SRI) has been known in Indonesia since 1999. However, there are some difficulties in utilizing SRI water management recommendations in the field, particularly in combination with organic nutrient management. While many demonstrations have given impressive gains in productivity, many farmers remain skeptical about applying this system. The current study was carried out to analyze water balance components in SRI paddy fields when applying intermittent irrigation. The experiment was conducted in Gabus Wetan village, Indramayu District, West Java, Indonesia from 17 Nov 2016 to 1 March 2017. We involved a local farmer who had been trained in SRI methods at an Organic SRI Center on how to conduct organic SRI management in his fields. Weather and soil sensors were set up in the fields to acquire data on daily field conditions as well as on plant growth. Data on weathers such as precipitation, air temperature, relative humidity, and wind speed were collected automatically during the season every 60 min, as well as the soil water depth. Analyzing the data collected, water balance analysis was well performed with low error (1.00%) in which the water inflows through precipitation and irrigation were 560 mm and 865 mm, respectively, while the outflows by crop evapotranspiration, percolation, and runoff were 430, 306 and 675 mm, respectively. Compared to conventional rice farming as commonly practices by applying continous flooding irrigation, water productivities of organic SRI were 30% and 27% higher with respect to total water input (WPIR) and with respect to the amount of evapotranspiration (WPET, respectively. Organic SRI produced 33% higher yield than that the average of conventional methods in the same subdistrict. The key was intermittent irrigation by maintaining shallow water depth (nearly soil surface) in the vegetative and generative stages. Therefore, it is an attractive option to farmers in irrigated areas where water resources is limited due to regional climate change effects. Keywords: